2018
DOI: 10.1371/journal.pntd.0006709
|View full text |Cite
|
Sign up to set email alerts
|

Field-collected Triatoma sordida from central Brazil display high microbiota diversity that varies with regard to developmental stage and intestinal segmentation

Abstract: Background/MethodologyTriatomine bugs are the vectors of Trypanosoma cruzi, the agent of Chagas disease. Vector control has for decades relied upon insecticide spraying, but insecticide resistance has recently emerged in several triatomine populations. One alternative strategy to reduce T. cruzi transmission is paratransgenesis, whereby symbiotic bacteria are genetically engineered to produce T. cruzi-killing proteins in the vector’s gut. This approach requires in-depth knowledge of the vectors’ natural gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 73 publications
5
58
3
Order By: Relevance
“…Some of our findings contradict the patterns reported by other authors. The most conspicuous example is the ontogenetic decrease of microbiome diversity in North American species, which is supported by Mann et al [40], but contrasts two studies on South American species [38,43]. Oliveira et al [38], reported an increase in microbiome diversity throughout ontogenetic development in T. sordida and Waltmann et al [43] found no ontogenetic effect in T. infestans.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 97%
See 4 more Smart Citations
“…Some of our findings contradict the patterns reported by other authors. The most conspicuous example is the ontogenetic decrease of microbiome diversity in North American species, which is supported by Mann et al [40], but contrasts two studies on South American species [38,43]. Oliveira et al [38], reported an increase in microbiome diversity throughout ontogenetic development in T. sordida and Waltmann et al [43] found no ontogenetic effect in T. infestans.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 97%
“…Previous studies on triatomine microbiomes have provided inconsistent and mutually conflicting results. They have suggested various factors, including ontogeny [38,42], species identity [36,40,42,43,92], sex [34,40], blood meal source [34], and T. cruzi infection [23,35,39,40], as determinants of microbiome composition, whilst another study claimed triatomine microbiomes have no determining factor [33]. Since many were based on limited sample size (e.g.…”
Section: Consistency Of the Patterns: Biology Vs Methodologymentioning
confidence: 99%
See 3 more Smart Citations